2015
DOI: 10.3109/0142159x.2015.1006605
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of bilingual English-Arabic version of Schutte self report emotional intelligence scale in an undergraduate Arab medical student sample

Abstract: Emotional intelligence is a multifactorial construct (three factors). The bilingual version of the SSREIS is a valid and reliable measure of trait emotional intelligence in an undergraduate Arab medical student population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
2
11
1
Order By: Relevance
“…Our study indicated a significant relation and a positive correlation between Emotional intelligence and lack of development, and between emotional intelligence and neglect, while no significant relation was found between emotional intelligence and overload, a previous study demonstrated a relation between all three components of burnout syndrome and overall emotional intelligence among surgery residents [30], another indicated to high emotional intelligence as protective factor against burnout among surgery residents as well [31][32][33], while the scores of EI were weakly correlated with decreased burnout in a study on oncology residents [34]. Emotional intelligence has mediation effect between emotional labour and burnout as was reported in one study on nurses [35].…”
Section: Discussionsupporting
confidence: 42%
“…Our study indicated a significant relation and a positive correlation between Emotional intelligence and lack of development, and between emotional intelligence and neglect, while no significant relation was found between emotional intelligence and overload, a previous study demonstrated a relation between all three components of burnout syndrome and overall emotional intelligence among surgery residents [30], another indicated to high emotional intelligence as protective factor against burnout among surgery residents as well [31][32][33], while the scores of EI were weakly correlated with decreased burnout in a study on oncology residents [34]. Emotional intelligence has mediation effect between emotional labour and burnout as was reported in one study on nurses [35].…”
Section: Discussionsupporting
confidence: 42%
“…Items are scored on a five-point Likert scale from 1 (Completely Disagree) to 5 (Completely Agree). Previous studies reported high Cronbach's alpha values for the SEIS [19,20].…”
Section: Ei Intervention and Instrumentsmentioning
confidence: 83%
“…Age: □Under 20 If your case is suitable for case work, would you like to do so? □ willing □ unwilling Note::The following lists the problems that you may encounter.…”
Section: Appendixmentioning
confidence: 99%
“…Finally, the trait level refers to habitual dispositionswhat people usually do when dealing with emotional situations [9]. The Trait model envisages EI as ''a constellation of emotional selfperceptions located at the lower levels of personality'' [10]; it refers to an individual's self-perceptions of their emotional abilities.…”
mentioning
confidence: 99%
“…Several studies assessed the EI in Arabic Countries into both perspectives: the trait and or ability [3], [10], [13], [23] - [27]. In Lebanon, the role of emotions in the formation of young students has been scarcely studied.…”
mentioning
confidence: 99%